'Hitler Must be Laughed At!': The PCA, Propaganda and the Perils of Parody During Wartime. Issue 4 (2nd October 2019) - Webb, Brandon
Abstract : During World War II Hollywood released several anti-fascist comedies that ignited an industry debate over the acceptable limits of 'permissible parody' during wartime. When reviewing these films, many critics fretted over whether comedy was an appropriate mode of representation for probing fascism's power dynamics. This debate took place within a broader discussion about aesthetics, progressive politics, and mass media in a time of war. This essay analyzes how the production and reception of anti-fascist comedies were shaped by the twin pressures of war and censorship. The period's film criticism will be placed within a larger social context that included the industry's self-censoring Production Code Administration (PCA), and the propagandizing mandate of the Office of War Information (OWI), the wartime agency tasked with communicating the Roosevelt administration's war aims through media. By examining studio correspondence with the PCA, official OWI documents and panel discussions from the 1943 Writers' Congress, I argue that a patriotic decorum grounded in universalism and realism emerged in the latter years of the war as the dominant mode of anti-fascist representation. Ironically, this patriotic decorum ignored how audiences processed war-themed content while eliding how censors, critics, and propagandists positioned the medium as a vehicle for wartime propaganda.